Crystal Structure and Biological Evaluation of Two Novel Organic-Inorganic Hybrid Materials as Antitumor Agents in the Treatment of Liver Cancer - Bao-Hua Song; Chen Li; Gui-Feng An (Journal of Chemistry)
Two novel organic-inorganic hybrid materials {(Hbiz)6[AsIII2AsVMoVI18O62]}·H2O (1, biz = benzimidazole) and (dim)[AsIII2AsVMoVI18O62] [2, dim = 1,6-bis(imidazol)hexane] have been successfully obtained by using the molybdenum arsenate and different N donor organic compounds and determined through X-ray single-crystal diffraction technique. The in vitro cytotoxicity of compounds 1 and 2 was then investigated against three human liver tumor cell lines (SMMC7721, Bel-7402, and MHCC97) by MTT assay. It was found that the two compounds showed potent use as antitumor agents against the aforementioned cell lines.